The Mechanism of Nerve Impulses: A Narrative Literature Review - Asri, Jhoni; Rumantir, Christ (Phlox Institute: Indonesian Medical Research Organization, 2023)
Neurons are not physically continuous with each other but form points of contact with adjacent neurons by special structures called synapses. The synapse consists of a small rounded end of the presynaptic neuron (synaptic knob) that is separated from the postsynaptic neuron by the synaptic cleft. This literature review aimed to describe the mechanism of nerve impulses in the human body. Neurons generate and conduct electrical impulses by selectively changing the conductance across their plasma membranes and influencing other nearby neurons by releasing chemical signals (neurotransmitters). Neurotransmitters are synthesized in neurons and in localization at the presynaptic terminal (synaptic boutons). The neurotransmitter is released into the synaptic cleft in response to the arrival of an electrical impulse and binds to receptor sites (binding sites) on the postsynaptic membrane of adjacent neurons or other effectors. In conclusion, an understanding of the impulse mechanism of nerves will assist in determining the treatment of neurological disorders.